DEVELOPMENT OF HONEYCOMB CORE FROM NATURAL AND TROPICAL WOOD FIBER FOR STRUCTURAL APPLICATION - ZAIDI, NURULJANNAH (IRC, 2017)
This paper discusses the development of honeycomb core from natural fiber. Honeycomb structures are commonly used as the cores of sandwich panels due to its high strength and lightweight characteristic. Empty fruit bunches (EFB) are biomass waste generated from the processing of palm oil. Studies shows that vast amount of by-products from agriculture sector are under-utilized and has vast potential for value added products. The study aims to develop natural paper honeycomb core and analyse on its quality in comparison to the commercialized Nomex honeycomb. The development of the honeycomb core is done through expansion method that is conducted manually. From the study, it is discovered that the EFB paper is unsuitable for honeycomb development. On the other hand, Kenaf paper is very suitable for honeycomb development.